Joanna Upton - Building climate resilience to escape chronic poverty - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
Keynote: 'Building resilience to avoid and escape chronic poverty: From theoretical foundations to practical applications' by Joanna Upton, from Cornell University. Filmed at the annual Science meeting of the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) from 7-11th April, San Lorenzo del Escorial, Spain. For more information visit the CCAFS website: http://www.ccafs.cgiar.org